1997
DOI: 10.1016/s0741-5214(97)70328-8
|View full text |Cite
|
Sign up to set email alerts
|

The glycoprotein IIb/IIIa antagonist c7E3 inhibits platelet aggregation in the presence of heparin-associated antibodies

Abstract: The GP IIb/IIIa receptor antagonist, c7E3, inhibits HAAb-induced platelet aggregation via a mechanism that does not appear to interfere with the binding between heparin and HAAb. Clinical trials are warranted to assess whether GP IIb/IIIa antagonists may allow patients with HAAb to safely receive heparin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…5 Platelet function inhibitors such as aspirin and dipyridamole protect patients with HAAbs from thromboembolic complications during brief exposures to heparin, but not from thrombocytopenia. 6 The glycoprotein IIb/IIIa inhibitor abciximab inhibits HAAb-induced platelet aggregation, 7 but the glycoprotein IIb/IIIa inhibitors have not been shown to provide adequate anticoagulation as the sole agent in patients with HAAbs. Certain glycoproteins IIb/IIIa inhibitors, such as abciximab, have been associated with thrombocytopenia and hemorrhagic complications.…”
Section: Discussionmentioning
confidence: 99%
“…5 Platelet function inhibitors such as aspirin and dipyridamole protect patients with HAAbs from thromboembolic complications during brief exposures to heparin, but not from thrombocytopenia. 6 The glycoprotein IIb/IIIa inhibitor abciximab inhibits HAAb-induced platelet aggregation, 7 but the glycoprotein IIb/IIIa inhibitors have not been shown to provide adequate anticoagulation as the sole agent in patients with HAAbs. Certain glycoproteins IIb/IIIa inhibitors, such as abciximab, have been associated with thrombocytopenia and hemorrhagic complications.…”
Section: Discussionmentioning
confidence: 99%
“…More than 66% of patients with HAAb will not cross-react to enoxaparin, 21 and 74% will not cross-react to dalteparin. 22 If the LMWH caus-es platelet aggregation and heparin-like anticoagulation therapy is required, we consider blocking the platelet glycoprotein IIb/IIIa receptor with a monoclonal antibody 23 or alternatively using a heparin substitute. A few patients with HIT have been treated with heparin substitutes (i.e., LMWHs, 21 heparinoids, 24 hirudin, 25 ancrod).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of the production of tissue factor at the surface of endothelial cells by serum samples from HIT patients suggested that immune injury to endothelial cells may have a role in the development of thrombosis in some patients after heparin therapy (7). To date, attempts to treat HIT with platelet function inhibiting agents such as aspirin, dipyridamole and iloprost have met with variable success and it is only recently that agents that bind to the GP IIb-IIIa receptor have been shown to inhibit platelet aggregation in the presence of heparin and heparin-associated antibodies (8)(9)(10). These data described that GP IIb-IIIa inhibitors can potently block in vitro platelet activation and aggregation induced by HIT serum/heparin and suggested that they can be used for the treatment of patients with HIT or as prophylaxis for HIT in those who are likely to produce a HIT response.…”
Section: Introductionmentioning
confidence: 99%